A NOVEL LARGE HOMOZYGOUS DELETION IN THE CELLULAR RETINALDEHYDE-BINDING PROTEIN GENE (RLBP1) IN A PATIENT WITH RETINITIS PUNCTATA ALBESCENS. Issue Volume 14:Issues 1(2020) (2020) - Bagheri, Saghar; Pantrangi, Madhulatha; Sodhi, Simrat K.; Bagheri, Sayeh; Oellers, Patrick; Scholl, Hendrik P. N.
Abstract : Purpose: To report the phenotypic and genotypic data of a patient with retinitis punctata albescens carrying a novel deletion in the RLBP1 gene. Results: A woman of Iranian descent in her forties with a history of progressive visual deterioration since early childhood exhibited phenotypic features of retinitis punctata albescens with multiple white dots in the posterior pole and macular atrophy in both eyes. The microarray analysis identified a ∼2.160 kb homozygous deletion corresponding to a minimum deletion boundary of chr15q26.1:89, 756, 882-89, 759, 041/GRCh37 (hg19), which encompasses exon 6 of the RLBP1 gene. Conclusion: We describe a novel large homozygous deletion in the RLBP1 gene encoding the cellular retinaldehyde-binding protein in a patient of Iranian descent with retinitis punctata albescens. Genotype–phenotype studies may provide more information about the functions of the RLBP1 encoding proteins and the disease course, because RLBP1 mutations are associated with high phenotypic variability and are therefore a necessity for future tailored individual therapies. Abstract : The authors report phenotypic and genotypic data of a patient of Iranian descent with retinitis punctata albescens carrying a novel deletion in the RLBP1 gene, providing useful information for individualized future gene therapy.